Speciation of mercury in environmental samples - Ruiz , Wilder Leonardo Gamboa (2018)
Mercury is one of the most toxic elements impacting on human and ecosystem health and therefore is one of the most studied environmental pollutants. All mercury species are toxic, with organic mercury compounds generally being more toxic than inorganic species. For this reason, the assessment of mercury distribution in environmental samples is a key task in analytical chemistry. Reverse phase chromatography (RPC) coupled to a UV post-column oxidation system and vapor generation atomic fluorescence spectrometry was optimised for the speciation and determination of inorganic and organic mercury (methylmercury and ethylmercury) in the form of APDC complexes. The mercury-APDC complexes were separated on a reverse phase column and oxidized on-line with a UV source. Hg2+ was selectively detected by AFS after reduction with stannous chloride to Hg0. The mobile phase composition was modified to include the simultaneous detection of EtHg+ by optimising the MeOH – Water to a 75:25 ratio. Quality parameters for the analytical method were established and a short-term stability study for EtHg+ was undertaken. Investigations are described to select the most suitable pre-treatment procedure for mercury speciation in polluted sediment samples. Five different pre-treatment procedures were evaluated: freezing at -80 and -20 °C, air drying, oven-drying at 40 °C, and lyophilization. Total mercury determination was performed with an aqua regia extraction, while for mercury speciation a method formerly optimized for the speciation of Hg2+ and MeHg+ was used in the analysis of sediments. The chromatogfraphic system consists on a reverse phase column (C18), with a mobile phase composed of (80:20) MeOH – water containing APDC 0,0015M as complexing agent and HN4Ac 0,01M at pH 5,5. For total mercury measurement, best results were obtained when the sediments were dried (air dried, oven-dried or lyophilized) because frozen samples showed lower concentration of total mercury. In the case of speciation analysis, MeHg+ was not detected in the sediment samples. Significant differences were found in the Hg2+ concentration among the samples subjected to the studied pre-treatments, even if there is no evidence suggesting that one pre-treatment preserves better the original speciation information was found.